Catalisadores de argila bentonítica Na35 para produção de biodiesel - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
The search for alternative and renewable sources of energy has been intensified due to energy and environmental problems. Biomass is considered a renewable source of energy and can be used to produce biofuels. Biodiesel is a biofuel that can be made of vegetable oils, through the transesterification reaction of triacylglycerides with methanol in the presence of either a homogeneous or heterogeneous catalyst. Heterogeneous catalysts present some advantages, such as: easy recovery after the transesterification reaction, potential to reuse and reduction in the purification steps. However, for a high conversion rate, higher temperature and longer reaction time are required when compared to the homogeneous catalysis. For this reason, many heterogeneous catalysts have been investigated. Therefore, this study proposed the chemical modification of Na35 bentonite clay (acid activation and pillarization) aiming at using it in the processes of residual oil clarification and biodiesel production. Samples of natural and activated clays with nitric acid and phosphoric acid were characterized using thermogravimetric and differential scanning calorimetric (TG/DSC), isotherms of N2 absorption/desorption and BET-BJH models, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD and SEM analysis showed that the acid activation provoked structural changes in the clay. The process of acid activation of bentonite Na35 clay and pillarization altered its structural properties resulting in an increase in pore volume and acid sites, increasing the specific superficial area and pore size. Next, these catalysts were used to obtain biodiesel through heterogeneous catalysis. The biodiesel obtained was characterized through RMN 1H and presented over 96.5% conversion rate in fatty acids methyl esters, showing the efficiency of pillared Na35 bentonite catalysts in the production of biodiesel.
Keywords: ativação ácida; pilarização; sítios ácidos; acid activation; pillarization; acid sites; CNPQ::CIENCIAS AGRARIAS